The importance of accounting for atmospheric effects in satellite remote sensing: a case study from the lower thames valley area, UK - Hadjimitsis, Diofantos G.; Clayton, Chris R I; Hope, V. S. (My University, 2000)
Solar radiation reflected by the Earth's surface to setellite sensors is modified by its interaction with the atmosphere. The objective of atmospheric correction is to determine true surface reflectance values by removing atmospheric effects from satellite images. Atmospheric correction is arguably the most important part of the pre-processing of satellite remotely sensed data and any omission produces erroneous results. The effects of the atmosphere are more severe for dark targets such as water reservoirs. The paper presents two methods of assessing the need for atmospheric correction, and addresses the importance of removing atmospheric effects in the satellite remote sensing of large reservoirs
Keywords: Atmospherics; Atmosphere; Remote sensing; Solar radiation; Meteorological satellites